EVALUASI PEMBELAJARAN MATEMATIKA MENGGUNAKAN PENDEKATAN BERBASIS PROYEK (PROJECT-BASED LEARNING) KELAS VIII DI SMP AL MUNIR TAMBUN UTARA - Rhisma Putri Oktaviani; Hendro Prasetyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the implementation of Project-Based Learning (PjBL) in mathematics for eighth-grade students at SMP Al Munir Tambun Utara. The research was motivated by the need to improve students’ understanding, motivation, and active participation in mathematics learning, which are often limited by conventional teaching methods. This research employed a qualitative descriptive method involving classroom observations, student worksheets, and interviews with teachers and students. The data were analyzed through stages of data reduction, presentation, and conclusion drawing. The findings indicate that the PjBL approach significantly enhances students’ conceptual understanding and problem-solving skills. Students demonstrated higher engagement, creativity, and collaboration during project activities, and teachers reported that PjBL facilitated contextual learning experiences. However, challenges were identified in time management and students’ initial adaptation to independent learning. Overall, PjBL is effective in fostering meaningful learning and critical thinking in mathematics classrooms.